2021
DOI: 10.4269/ajtmh.20-1386
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Burkholderia pseudomallei from Localized Pyogenic Infections in Eastern India: A Clinico-Microbiological Study

Abstract: Melioidosis, caused by Burkholderia pseudomallei, is increasingly recognized in several regions of the globe. The present study was performed to identify and determine the frequency of B. pseudomallei infection in localized pyogenic lesions in eastern India and describe their clinico-microbiological profile. Pus samples were subjected to standard microbiological techniques for isolation and identification of various bacteria, including B. pseudomallei, which were confirmed by PCR. The clinical and demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, he was a resident of a TB endemic zone and a farmer by occupation, which made him prone to melioidosis, which is common in irrigated areas such as rice paddies 6 . There are few cases of melioidosis reported from our state earlier 9,18,21,22 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, he was a resident of a TB endemic zone and a farmer by occupation, which made him prone to melioidosis, which is common in irrigated areas such as rice paddies 6 . There are few cases of melioidosis reported from our state earlier 9,18,21,22 .…”
Section: Discussionmentioning
confidence: 93%
“…Simple tests that can aid in the identification of B. psedudomallei include the typical colony characteristics on MacConkey agar (nonlactose fermenting, small, smooth colonies after overnight incubation turning pink with a metallic sheen after 48 hours and dry wrinkled after 96 hours), “safety-pin” appearance due to typical bipolar staining on Gram stain, and inherent resistance to polymyxins and gentamicin (tested by colistin 10 μg, polymyxin B 300U, and gentamicin 10 μg disks). Newer tests that can help include the commercially available identification systems (Phoenix, Microscan walkway 96, Vitek-2) and matrix-assisted laser desorption ionization mass spectrometry 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Informative case series have been published from Tamil Nadu [18], Kerala [19] and Karnataka [20] in southern India and Odissa in eastern India [21]. An extensive soil sampling study from southwest India showed the wide environmental distribution of B. pseudomallei but with considerable differences in abundance between sites and within single sites, the highest abundance during the rainy season and the presence of B. pseudomallei linked to nutrient-depleted habitats [22 ▪ ].…”
Section: Epidemiologymentioning
confidence: 99%
“…In China, meliodosis is prevalent in regions such as Hainan, Guangdong, Guangxi, Fujian, Hong Kong, and Taiwan, with Hainan being the epicenter of the epidemic [ 3 ]. While melioidosis affects multiple organs, with the lungs and bloodstream being the most commonly infected [ [4] , [5] , [6] ], cases involving the pancreas are exceptionally rare. Our literature search identified 11 reported cases of melioidosis with pancreatic involvement, all of which were distributed in Asia [ [7] , [8] , [9] , [10] , [11] , [12] ], including five from India [ 8 , 10 , 12 ], four from Brunei [ 7 ] and two from China [ 9 , 11 ] ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%